2004
DOI: 10.2298/mpns0402045p
|View full text |Cite
|
Sign up to set email alerts
|

Fosinopril and amlodipine in the treatment of isolated systolic hypertension

Abstract: The aim of this study was to assess the therapeutic effects of fosinopril (F) and amlodipine (A) on regulation and circadian rhythm of blood pressure, and to evaluate left ventricle mass index (LVMI) in patients over 60 years of age with isolated systolic hypertension, after three months of administration period. After one-week placebo run-in period, 60 patients were randomized into two groups, each including 30 patients, to receive either fosinopril or amlodipine for three months. Clinical, echocardiographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Thus both positive and negative regulators, in the form of auxiliary proteins, influence ultimate I Ca,L density. Ca 2ϩ channel blockers (CCBs) are frequently used to regulate blood pressure in hypertensive patients (22,32,38); however, little is known about the long-term cardiac effects of these drugs on cardiac myocytes. The primary objective of this study was to test the hypothesis that cardiac I Ca,L is homeostatically regulated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus both positive and negative regulators, in the form of auxiliary proteins, influence ultimate I Ca,L density. Ca 2ϩ channel blockers (CCBs) are frequently used to regulate blood pressure in hypertensive patients (22,32,38); however, little is known about the long-term cardiac effects of these drugs on cardiac myocytes. The primary objective of this study was to test the hypothesis that cardiac I Ca,L is homeostatically regulated.…”
mentioning
confidence: 99%
“…Overall, Ca V ␤ 2 in the heart serves as a positive regulator of I Ca,L (11). We recently showed (13,19) (22,32,38); however, little is known about the long-term cardiac effects of these drugs on cardiac myocytes. The primary objective of this study was to test the hypothesis that cardiac I Ca,L is homeostatically regulated.…”
mentioning
confidence: 99%
“…To our knowledge, this is the first clinical report comparing the efficacy of fosinopril and amlodipine in the treatment of children with primary hypertension. PavlovićK et al found no difference in BP control rates between fosinopril or amlodipine monotherapy for 3 months in patients older than 60 years with isolated systolic hypertension (76.6% vs. 79.9%) ( 27 ). Similar to their results, we found no difference in BP control rates between the two groups, but a 10% difference in the degree of SBP and DBP reductions, although this difference was no longer significant after adjustment.…”
Section: Discussionmentioning
confidence: 99%